Carbon Emission Disclosure and Corporate Value: Does Company Size Play a Critical Role? - Susi Susilawati; Nova Rini; Ridwan Saleh; Maria Suryaningsih (Politeknik Raflesia Press, 2025)
This research aims to analyze the effect of carbon emissions disclosure on firm value by considering the company size factor as a moderating variable. The data analysis used is balanced panel data regression. The sample of non-financial companies was selected based on the specified criteria. The research results indicate that carbon emission disclosure (CED) has a negative effect on firm value. Meanwhile, the company size moderates the positive impact of carbon emission disclosure on firm value. This research implies that disclosure of carbon emissions can damage a business's reputation., therefore concrete action is needed to comply with the regulations and quickly respond to the actions to reduce environmental damage resulting from their business activities. This research contributes to the accounting literature by emphasizing the importance of the quality and context of carbon emissions disclosure, especially in companies listed on IDX-IC shares.